Long-lasting effects of antibiotics on bacterial communities of adult flies. Issue 4 (3rd March 2020) - Ourry, Morgane; Lopez, Valérie; Hervé, Maxime; Lebreton, Lionel; Mougel, Christophe; Outreman, Yannick; Poinsot, Denis; Cortesero, Anne Marie
ABSTRACT: Insect symbionts benefit their host and their study requires large spectrum antibiotic use like tetracycline to weaken or suppress symbiotic communities. While antibiotics have a negative impact on insect fitness, little is known about antibiotic effects on insect microbial communities and how long they last. We characterized the bacterial communities of adult cabbage root fly Delia radicum in a Wolbachia -free population and evaluated the effect of tetracycline treatment on these communities over several generations. Three D. radicum generations were used: the first- and second-generation flies either ingested tetracycline or not, while the third-generation flies were untreated but differed with their parents and/or grandparents that had or had not been treated. Fly bacterial communities were sequenced using a 16S rRNA gene. Tetracycline decreased fly bacterial diversity and induced modifications in both bacterial abundance and relative frequencies, still visible on untreated offspring whose parents and/or grandparents had been treated, therefore demonstrating long-lasting transgenerational effects on animal microbiomes after antibiotic treatment. Flies with an antibiotic history shared bacterial genera, potentially tetracycline resistant and heritable. Next, the transmission should be investigated by comparing several insect development stages and plant compartments to assess vertical and horizontal transmissions of D. radicum bacterial communities. Abstract : Antibiotic treatment reduces but does not destroy fly bacterial diversity and its effects last over several generations in untreated flies.